2022
DOI: 10.3389/fchem.2022.1005727
|View full text |Cite
|
Sign up to set email alerts
|

Highlights in USP7 inhibitors for cancer treatment

Abstract: Ubiquitin-specific protease 7 (USP7) is a member of one of the most largely studied families of deubiquitylating enzymes. It plays a key role modulating the levels of multiple proteins, including tumor suppressors, transcription factors, epigenetic modulators, DNA repair proteins, and regulators of the immune response. The abnormal expression of USP7 is found in various malignant tumors and a high expression signature generally indicates poor tumor prognosis. This suggests USP7 as a promising prognostic and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Our studies indicated an accumulation of USP7 in the nucleus during the proangiogenic function of ACEI in ECs, where it binds to Sp1/Sp3 and protects Sp1/Sp3 from proteasomal degradation. Furthermore, USP7 inhibitor significantly abrogated the proangiogenic function of ACEI, indicating the adverse effect of potential drug aiming at USP7 61 . Phosphorylation of the Ser18 site by the kinase CK2 stabilizes USP7, thus contributing to the downstream stability of MDM2 in the nucleus 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Our studies indicated an accumulation of USP7 in the nucleus during the proangiogenic function of ACEI in ECs, where it binds to Sp1/Sp3 and protects Sp1/Sp3 from proteasomal degradation. Furthermore, USP7 inhibitor significantly abrogated the proangiogenic function of ACEI, indicating the adverse effect of potential drug aiming at USP7 61 . Phosphorylation of the Ser18 site by the kinase CK2 stabilizes USP7, thus contributing to the downstream stability of MDM2 in the nucleus 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Targeting the critical role of TOPORS in STUbL-driven cellular responses might provide a more specific and thus less toxic alternative to full inhibition of SUMOylation in some clinical contexts. In this regard, harnessing the notion that USP7 inhibitors, several of which display efficacy for cancer therapy in pre-clinical studies 56 , potently deplete TOPORS and recapitulate the consequences of TOPORS loss may be particularly useful. Further studies of the mechanisms of TOPORS STUbL function and how this may be exploited therapeutically are therefore well warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the increased mechanistic and structural characterisation of DUBs/ULPs with their targets or inhibitors, combined with deep sequencing of patient samples, either at the genomic or expression level, will likely enable more precise patient stratification with reduced likelihood of developing resistance. Current efforts to inhibit DUBs/ULPs are reviewed elsewhere in more detail [ 53 , 142 , 316–318 ]. Overall, an enhanced understanding of Ub/UBL signalling via DUBs and ULPs in DDR signalling will provide a stable grounding to develop targeted strategies for treating human diseases, such as cancers.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%